THE EFFECTS OF INQUIRY TRAINING LEARNING MODEL AND CRITICAL THINGKING ABILITY TOWARD SCIENCE PROCESS SKILLS OF SMA - Ferawati Hutapea; Motlan . (Jurnal Pendidikan Fisika, 2015)
The purpose of research are 1). To know are differences in science process skills of students with the applied of inquiry training learning model and direct instruction learning models, 2). To know are differences in science process skills of students who has high critical thinking ability and the  critically low ability, 3). To know the interaction inquiry training learning model and critical thinking ability toward students science process skills. The samples in this research conducted by cluster random sampling and  as many as two class , the first class (X-I) as experiment applied Inquiry Training learning model and the second class (X-2) as control class applied Direct Intruction learning model. The instrument used in this research is tests science process skills and critical thinking skills in the form of description and observation sheets science process skills. From these results it can be concluded that: 1) there are differences in students science process skills with applied inquiry training model and direct intruction model, 2) science process skills of students with high critical thinking ability is better than the science process skills of students with the ability to think critically low, and 3) the interaction inquiry training learning model and critical thinking ability toward the science process skills.